Kekuatan Hukum Jangka Waktu Surat Kuasa Membebankan Hak Tanggungan Kredit Mikro pada Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Nomor 22 Tahun 2017 - Ahmad Zulfikar (Wajah Hukum, 2019)
In providing credit, banks must be sure that the loaned funds must be able to be returned on time together with the interest and in accordance with the terms agreed upon jointly by the parties concerned in the credit agreement so that in the implementation of the credit agreement so that it can be carried out in a healthy and secure manner. For this reason, the issuance of Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 22 Year 2017 is because microcredit currently has high potential in the use of SKMHT and shows that in microcredit, banks as fund channeling institutions still need guarantees in providing credit facilities so that they are regulated regarding the period of the power of attorney to charge the mortgage up to the end of the principal credit. However, with this regulation, the power of attorney imposes a micro credit guarantee given not increased to the mortgage, the bank as the creditor in providing micro credit to the debtor generally does not control the objects which are physical collateral guarantees, but only has administrative rights. The notary must have extensive knowledge about SKMHT in order to adjust the SKMHT clause both micro and non-micro. With in-depth knowledge of power of attorney, the Notary can ask the client. In this case the Notary's role is to direct the client in the contents of SKMHT so as not to conflict with the law, public order and decency. The agreement must be based on consensus or agreement from the parties that made it. Furthermore, the notary's function in preventing the duration of the power of attorney to charge micro credit dependents can be done by utilizing his position as one of law enforcers by providing legal counseling and to banks.